'Adaptive Migration:' Climate Change, Climate Migration, and Climate Adaptation in Peru’s Highlands Communities - Karsten Paerregaard (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies)
In the current debate about climate-induced migration some scholars argue that rather than understanding migration as a failure to cope with climate change, we should view it as a means of adapting to it. To scrutinize this argument and assess the applicability of the notion of “adaptive migration” the paper examines the role migration plays in the climate adaptation of Peru’s highland communities. Drawing on research in two communities located in the country’s southwestern highlands, it shows how climate change impacts agriculture and water management threatening the villagers’ lives and livelihoods. It also investigates the communities’ climate adaptation options and discusses how the villagers deal with them. Moreover, the paper explores how migration intersects with these options especially regarding crop shifts and reorganization of irrigation routines. Lastly, it discusses the range of activities migrants engage in in their home communities highlighting those that contribute to climate adaptation. The paper argues that given that all migrations entail a process of adaptation, the term “adaptive migration” is redundant. Even so, the paper’s data suggest that returning migrants sometimes act as promotors and implementors of climate adaptation. To foreground these migrants, the paper encourages scholars to apply the term “migratory adaptation” instead of “adaptive migration.” Abstracta En el debate sobre la migración inducida por el cambio climático algunos investigadores sostienen que la migración posibilita que gente viviendo en sitios vulnerables al clima pueden quedarse en sus comunidades en vez de huir. Para escrutar este argumento y evaluar la aplicabilidad de la noción de “migración adaptiva” este artículo examina el papel que la migración juega en la adaptación climática de las comunidades de la sierra peruana. Revisando datos de investigación en dos comunidades en el sur del Perú el artículo muestra cómo el cambio climático impacta la agricultura y el manejo del agua poniendo la vida y el sustento de los comuneros en peligro. También investiga las opciones que ellos tienen para adaptarse al cambio climático y discute cómo los comuneros las manejan. Por fin explora el enlace entre la migración y estas opciones enfocando en el cambio de cultivo y la reorganización del riego. El artículo sostiene que todas las migraciones implican un proceso de adaptación. Por lo tanto, el término “migración adaptiva” es redundante. No obstante, los datos muestran que algunos migrantes de retorno contribuyen a la adaptación climática. Para empatizar su papel el artículo sugiere que aplicamos el término “adaptación migratoria” en vez de “migración adaptativa.” Palabras Claves: Perú; cambio climático; adaptación; migración; agricultura; agua